The Legal Consequences of Mystery Box Purchase and Sale Transactions Based on the Disclosure Concept - Muhammad Amin; Muh. Imaduddin Akbar; Bhismoadi Tri Wahyu Faizal; Rizka Amaliyah Maghfiroh (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
This research explores the legal implications of the widespread online practice of buying and selling mystery boxes, acknowledged as commonplace by consumers and businesses. The aim is to analyze the legal consequences of mystery box buying and selling contracts on several popular marketplaces among the millennial generation. Despite the unclear nature of the transaction's object, buyers are prepared and understand the contents of the mystery box. The study employs a normative legal approach with analytical descriptive methods. The findings conclude that transactions involving mystery boxes are considered fasid contracts due to their failure to meet the prerequisites for a valid bai' as-salam contract. This deficiency includes the absence of clarity in the object's value, certainty, existence, transferability, mutual knowledge, and exemption from maysir and gharar. Furthermore, the consumer's proclamation as a mystery box buyer is deemed inconsistent with the interāḍin concept outlined in Surah An-Nisa verse 29, which emphasizes the necessity of clear specifications for goods to avoid speculation. The study also highlights the potential for sellers to exploit the mystery box concept as an opportunity to conceal deficiencies in the items being sold.